Pan-European atmospheric lead pollution, enhanced blood lead levels, and cognitive decline from Roman-era mining and smelting - Joseph R. McConnell; Nathan J. Chellman; Andreas Plach; Sophia M. Wensman; Gill Plunkett; Andreas Stohl; Nicole-Kristine Smith; Bo Møllesøe Vinther; Dorthe Dahl-Jensen; Jørgen Peder Steffensen; Diedrich Fritzsche; Sandra O. Camara-Brugger; et al. (Proceedings of the National Academy of Sciences, 2025)
Ancient texts and archaeological evidence indicate substantial lead exposure during antiquity that potentially impacted human health. Although lead exposure routes were many and included the use of glazed tablewares, paints, cosmetics, and even intentional ingestion, the most significant for the nonelite, rural majority of the population may have been through background air pollution from mining and smelting of silver and lead ores that underpinned the Roman economy. Here, we determined potential health effects of this air pollution using Arctic ice core measurements of Roman-era lead pollution, atmospheric modeling, and modern epidemiology-based relationships between air concentrations, blood lead levels (BLLs), and cognitive decline. Findings suggest air lead concentrations exceeded 150 ng/m 3 near metallurgical emission sources, with average enhancements of >1.0 ng/m 3 over Europe during the Pax Romana apogee of the Roman Empire. The result was blood lead enhancements in young children of about 2.4 µg/dl above an estimated Neolithic background of 1.0 µg/dl, leading to widespread cognitive decline including a 2.5-to-3 point reduction in intelligence quotient throughout the Roman Empire.